Comparison of death anxiety, self-concept and attitudes to old age in the elderly living on their own, residing in nursing homes full-time or part-time, or living with extended families in Kermanshah, Iran - Momeni, Khodamorad; Karami, Jahangir; Rafiee, Zahra (Researcher Bulletin of Medical Sciences, 2019)
Background and Objective: Old age is an important period of life, and paying attention to the issues and needs of this course is a social necessity. Therefore, the present study aimed to compare death anxiety, self-concept and attitudes to old age in the elderly living on their own, residing in nursing homes full-time or part-time, or living with extended families in Kermanshah, Iran. Materials and Methods: In this descriptive and causal-comparative study, the statistical population consisted of the elderly living on their own, residing in nursing homes full-time or part-time, or living with extended families in Kermanshah, Iran over 2016-2017. A total of 304 subjects were selected through random sampling and convenience sampling. As for data collection, three questionnaires were employed: Templer’s Death Anxiety Scale (1970), Beck’s Self-concept Inventory (1990), and Kogan’s Attitudes toward Older People Scale (KAOPS) (1961). Results: The mean scores of just death and general factor of the variable of death anxiety and the mean scores of negative and positive attitudes of the elderly residing in nursing homes full-time were lower than those of other groups. In addition, the mean score of self-concept of the elderly living on their own was higher than those of other groups. Discussion and Conclusion: The levels of death anxiety and attitudes towards old age in the elderly residing in nursing homes were lower than those in other groups. It was also concluded that the level of self-concept of the elderly living on their own was higher than those of other groups.